EUS-guided Gastroenterostomy: Assessing the Competence of the Endoscopist - Jena, Anuraag; Rana, Surinder Singh (Journal of Digestive Endoscopy, 2020)
Assessing competence is of utmost importance for complex EUS procedures like EUS-guided gastroenterostomy (EUS-GE) that are associated with higher risk of procedural complications. It is a matter of intense debate on what is the training needed to carry out these interventions, how to judge for competence, and who can perform these newer interventions. The procedure has several variations including the methods to identify the jejunal loops on EUS like direct puncture, balloon-assisted, and hybrid rendezvous with ultrathin endoscope. Therefore, there is lack of clarity on the role and ways of assessing the learning curve for EUS-GE. In this news and views, we are discussing two studies that assessed the learning curve for EUS-GE.
Keywords: endosonography; stomach; gastric outlet obstruction